2014
DOI: 10.1091/mbc.e14-04-0865
|View full text |Cite
|
Sign up to set email alerts
|

Nup50 is required for cell differentiation and exhibits transcription-dependent dynamics

Abstract: Nup50 is a mobile nucleoporin with a pronounced presence both at the nuclear pore complex and in the nucleoplasm that can move between these different localizations. The dynamic behavior of Nup50 in both locations is dependent on active transcription by RNA polymerase II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 50 publications
(85 reference statements)
3
48
0
Order By: Relevance
“…Consistent with such a notion, previous research in human cells demonstrated that a subset of peripheral Nups can move on and off human NPCs, raising the possibility that Nups' influence on gene expression could extend beyond genomic regions associated with the NE (Rabut et al 2004). Supporting this hypothesis, the dynamic movement of a subset of Nups, including Nup50, Nup98, and Nup153, was slowed in the presence of transcriptional inhibitory drugs, suggesting a role for Nup98 and potentially other Nups in the regulation of transcription (Griffis et al 2002(Griffis et al , 2004Buchwalter et al 2014). A breakthrough in our understanding of the function of mobile Nups came from studies in Drosophila and mammalian cells, which determined that Nup98 and several other peripheral Nups such as Nup50, Nup62, and Nup153 can detach from the NPC, bind to intranuclear promoters distal to the NE, and affect regulation of adjacent genes (Capelson et al 2010;Kalverda and Fornerod 2010;Liang et al 2013).…”
mentioning
confidence: 84%
“…Consistent with such a notion, previous research in human cells demonstrated that a subset of peripheral Nups can move on and off human NPCs, raising the possibility that Nups' influence on gene expression could extend beyond genomic regions associated with the NE (Rabut et al 2004). Supporting this hypothesis, the dynamic movement of a subset of Nups, including Nup50, Nup98, and Nup153, was slowed in the presence of transcriptional inhibitory drugs, suggesting a role for Nup98 and potentially other Nups in the regulation of transcription (Griffis et al 2002(Griffis et al , 2004Buchwalter et al 2014). A breakthrough in our understanding of the function of mobile Nups came from studies in Drosophila and mammalian cells, which determined that Nup98 and several other peripheral Nups such as Nup50, Nup62, and Nup153 can detach from the NPC, bind to intranuclear promoters distal to the NE, and affect regulation of adjacent genes (Capelson et al 2010;Kalverda and Fornerod 2010;Liang et al 2013).…”
mentioning
confidence: 84%
“…In addition, NPC components have been implicated in cell differentiation and cell identity maintenance Buchwalter et al 2014;Jacinto et al 2015). Here, we show Cont 5 that components of the NPC, such as Nup153 and Nup93, establish functional interactions with SE-associated genes, which are critical regulators of cell type-specific transcriptional programs.…”
Section: Nups Interact With Sesmentioning
confidence: 71%
“…The observed mobility of peripheral Nups is consistent with their ability to function away from the NPC as soluble regulatory modules. Interestingly, the mobility of Nups like Nup153, Nup98, or Nup50 is connected to RNA polymerase II (Pol II)-mediated transcriptional activity, indicating that off-pore Nups might actively participate in transcriptional regulation (Griffis et al 2002;Buchwalter et al 2014). Experimental support for this hypothesis was provided in Drosophila, where several Nups, such as Nup98, Nup50, Sec13, and Nup62, were found to bind specific chromatin regions in the nuclear interior (Capelson et al 2010;.…”
Section: Gene Expression Regulation In Metazoansmentioning
confidence: 99%
“…Interestingly, Nup98 target genes in human cells change during differentiation, likely influencing specific transcriptional programs as cell identity evolves (Liang et al 2013). Last, down-regulation of Nup50 or Gp210 abolishes the differentiation of mouse myoblasts to myotubes (D'Angelo et al 2012;Buchwalter et al 2014). In conclusion, considering the plasticity of Nup-mediated transcriptional control, it might be anticipated that Nups play a pivotal role in differentiation and development.…”
Section: Gene Expression Regulation In Metazoansmentioning
confidence: 99%